The electrocatalytic response of metallophthalocyanines when clicked to electrodes and to nanomaterials - Mpeta, Lekhetho Simon (Rhodes University, Faculty of Science, Department of Chemistry, 2021)
Conjugates of nanomaterials and metallophthalocyanines (MPcs) have been prepared and their electrocatalytic activity studied. The prepared nanomaterials are zinc oxide and silver nanoparticles, reduced graphene oxide nanosheets and semiconductor quantum dots. The MPcs used in this work are cobalt (II) (1a), manganese(III) (1b) and iron (II) (1c) 2,9(10),16(17),23(24)- tetrakis 4-((4-ethynylbenzyl) oxy) phthalocyaninato, 2,9(10),16(17),23(24)- tetrakis(5-pentyn-oxy) cobalt (II) phthalocyaninato (2), 9(10),16(17),23(24)- tris-[4-tert-butylphenoxy)-2- (4-ethylbezyl-oxy) cobalt (II) phthalocyaninato (3), 9(10),16(17),23(24)- tris-[4-tertbutylphenoxy)-2-(pent-4yn-yloxy)] cobalt (II) phthalocyaninato (4), cobalt (II) (5a) and manganese (III) (5b) 2,9(10),16(17),23(24)- tetrakis [4-(4-(5-chloro-1H-benzo [d]imidazol-2-yl)phenoxy] phthalocyaninato and 9(10),16(17),23(24)- tris tert butyl phenoxy- 2- [4-(4-(5-chloro-1H-benzo[d]imidazole-2-yl)phenoxy] cobalt (II) phthalocyaninato (6). Some of these MPcs (1a, 3 and 4) were directly clicked on azide grafted electrode, while some (1b, 1c, 2, 5a and 5b) were clicked to azide functionalised nanomaterials and then drop-dried on the electrodes. One phthalocyanine (5b) was drop-dried on the electrode then silver nanoparticles were electrodeposited on it taking advantage of metal-N bond. Scanning electrochemical microscopy, voltammetry, chronoamperometry, electrochemical impedance spectroscopy are among electrochemical methods used to characterise modified electrodes. Transmission electron microscopy, X-ray photoelectron spectroscopy, Xray diffractometry, Raman spectroscopy and infrared spectroscopy were employed to study surface functionalities, morphology and topography of the nanomaterials and complexes. Electrocatalytic activity of the developed materials were studied towards oxidation of 2-mercaptoethanol, hydrazine and hydrogen peroxide while the reduction study was based on oxygen and hydrogen peroxide. In general, the conjugates displayed superior catalytic activity when compared to individual materials. Complex 2 alone and when conjugated to zinc oxide nanoparticles were studied for their nonlinear optical behaviour. And the same materials were explored for their hydrazine detection capability. The aim of this study was to develop sensitive, selective and affordable sensors for selected organic waste pollutants. Conjugates were found to achieve the aim of the study compared to when individual materials were employed.
Keywords: Phthalocyanines; Nanostructured materials; Electrocatalysis; Nanoparticles; Environmental chemistry; Electrodes; Organic wastes -- Purification